IMPLEMENTASI ETIKA PROFESI GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA DIGITAL - Ahmad Khamdani; Khoirun Nisa; Muhammad Agus NurKholis; Muhlisin Muhlisin; Abul Mafaakhir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research stems from the increasing use of digital technology in the learning process, which requires teachers to adhere to professional ethics. Technological developments have brought changes to the learning system, both through the use of digital media and online learning interactions. The focus of this research is the continued discovery of learning practices that do not fully reflect the ethical values ​​of the teaching profession in the use of digital technology. This study aims to describe the application of professional ethics in teaching, identify obstacles encountered, and analyze efforts to improve the quality of learning in the digital era. The method used is a literature review utilizing various relevant scientific sources. The results show that the implementation of professional ethics in teaching is reflected in an attitude of responsibility, honesty, objectivity, and exemplary behavior in the use of learning technology. Thus, it is necessary to improve digital competence and strengthen the understanding of professional ethics to support the creation of effective and quality learning in the digital era.